Sistem Monitoring Ketersediaan Slot Parkir Berbasis Internet of Things (IoT) Menggunakan ESP32 dan Sensor Ultrasonik - Saenong, Andi; Hanapi, Khaerunnisa; Fitriani, Fitriani; Sartika, Sartika; Fettyana, Fettyana (TIN: Terapan Informatika Nusantara, 2026)
Limited real-time information on parking slot availability is one of the factors that causes vehicle queues, long parking search times, and potential congestion in parking areas of buildings, shops, and shopping centers. This study aims to develop an Internet of Things (IoT)-based smart parking system that is able to automatically detect parking slot availability and display information via a website in real-time. The system was developed using an ultrasonic sensor to detect the presence of vehicles in parking slots, an ESP32 microcontroller as a data processor and sender, a database as a slot status storage, a website as a monitoring medium, an LCD as a local information medium, and a servo motor as a parking barrier controller. The research method used is Research and Development (R&D) with a Prototyping model, which includes the stages of needs analysis, system design, prototype creation, implementation, testing, and evaluation. The test results show that the system is able to detect the status of empty and occupied parking slots, send data from the ESP32 to the database, and update the website display in an average of 2–3 seconds under stable network conditions. In addition, the system is able to automatically control the barrier based on parking slot availability. Based on the test results, the system achieved an average accuracy of 94.16%. Therefore, the developed smart parking system can be a more effective, efficient, automated, and easily accessible parking monitoring and management solution via the internet.